2018
DOI: 10.1002/cdq.12145
|View full text |Cite
|
Sign up to set email alerts
|

Breadth of Vocational Interests: The Role of Career Adaptability and Future Orientation

Abstract: The authors examined the relationship between career adaptability, future orientation, and vocational interests. Specifically, they tested the role of career adaptability and future orientation in promoting a broader range of vocational interests, based on the principle that experiencing more interests can be useful in giving one's best in multiple occupations and in planning a broad range of career goals. A total of 762 Italian adolescents (383 males, 379 females) participated in the study. Results highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Interventions must be aimed at supporting the daunting challenge of this transition and recovering from the psychological and vocational fallout of this pandemic. Even more, interventions should guarantee a positive orientation toward future vision promoting hope and optimism (Ginevra et al, 2018;Santelli et al, 2018) and enhancing the development of effective coping strategies (i.e., career adaptabilities, Savickas, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions must be aimed at supporting the daunting challenge of this transition and recovering from the psychological and vocational fallout of this pandemic. Even more, interventions should guarantee a positive orientation toward future vision promoting hope and optimism (Ginevra et al, 2018;Santelli et al, 2018) and enhancing the development of effective coping strategies (i.e., career adaptabilities, Savickas, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Career practices could encourage children to more flexibly use in‐breadth career exploration free from barriers defined by gender and socioeconomic status or the particular career interests defined by their parents' jobs (Gottfredson, 1996; Lee et al, 2015). Children's interaction with workers engaged in gender‐atypical jobs and/or those in different social classes would be important to foster children's career adaptability (Ginevra et al, 2018). This could be particularly important for boys and for children from less affluent backgrounds given findings suggesting their vulnerability to an early gender‐biased and prestige‐biased circumscription of occupational alternatives (Cadima et al, 2015; David et al, 2015; Joshi & Bakshi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has highlighted the capacity of the family to cultivate children's broad and deep interests as a protective factor from the anxiety triggered by contemporary society (Kenny, Blustein, & Meerkins, 2018). Thus, the family holds the potential to expand children's interests and to foster their career adaptability (Ginevra, Annovazzi, Santilli, Di Maggio, & Camussi, 2018). Previous research on children's career aspirations and expectations has suggested that parents can nurture children's enrollment in and exploration of multiple RIASEC environments (Liu et al, 2015; Oliveira et al, 2017).…”
Section: Parental Influence On Children's Career Aspirations and Expementioning
confidence: 99%
See 1 more Smart Citation
“…Campbell and Porquet (2015) reported that life satisfaction was negatively correlated to indicators of inequality and hard work conditions, as well as to underemployment and unemployment. As work engages most of our lives, decent work, together with career adaptability and positive variables such as resilience, is therefore essential for individuals' quality of life and life satisfaction (Ginevra et al, 2018). On the positive side, the chances of finding a good job can be increased by providing individuals with career adaptability resources (Koen et al, 2012;Skorikov, 2007).…”
Section: The Challenges Of Life Design In a European Contextmentioning
confidence: 99%